IMPLEMENTASI KEBIJAKAN PROGRAM BERAS MISKIN (RASKIN) DI KELURAHAN SULEWATANG KECAMATAN POLEWALI KABUPATEN POLEWALI MANDAR - Mukhlis Hannan (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2016)
This study aims to find out how the implementation of the rice distribution policy for the poor (raskin) in Sulewatang Sub-District, Polewali Mandar District, Polewali District. This type of research is quantitative, which describes the description of the implementation of micin rice distribution policies. Data is obtained through surveys, questionnaires, interviews, and documentation to collect as much data as possible from the field. Data were analyzed descriptively qualitatively which described systematically, factually and accurately about the facts obtained. The results showed that the implementation of a poor rice program policy in Sulewatang Urban Village had not yet achieved maximum results, because a number of things that were implemented were not in accordance with the existing rules/regulations. Even so, the goal is quite achievable because it can reduce the expenditure burden. The indicator of the success of the distribution of raskin / rastra seen from the process and mechanism using 6T (six right) is considered to be still less than optimal.